Protocol for assessing stakeholder engagement in the development and evaluation of the Informed Health Choices resources teaching secondary school students to think critically about health claims and choices - Nsangi, Allen; Semakula, Daniel; Ssenyonga, Ronald; Mugisha, Michael; Nyirazinyoye, Leaticia; Sewankambo, Nelson Kaulukusi (PLoS One, 2020)
As part of a five year plan (2019–2023), the Informed Health Choices Project, is developing and evaluating resources for helping secondary school students learn to think critically about health claims and choices. We will bring together key stakeholders; such as secondary school teachers and students, our main target for the IHC secondary school resources, school administrators, policy makers, curriculum development specialists and parents, to enable us gain insight about the context.